KAJIAN VARIASI MATRIK KOMPOSIT SERBUK SEKAM PADI LIMBAH TERHADAP SIFAT MEKANIK - Achmad Nurhidayat (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2020)
The use of powder-strength composite materials which has several advantages, has the potential to change the paradigm of other metallic or synthetic materials. This study aims to determine the effect of variations of the matrix on the mechanical strength of the composite of rice husk powder waste. The research method used was a destructive test, with the research procedure starting with 120 mesh waste rice husks, in an oven with a temperature of 110 ° C for 45 minutes to a moisture content of ± 4%. Furthermore, it is mixed with 60% BQTN polyester resin as much as 60% and 40% of rice husk powder waste. After that, stir for 6 minutes and add as much as 1% catalyst and stir again for 2 minutes. The mixture is poured in a wax-coated glass mold. Other matrix variations with EPR 174 type epoxy resin and R-802 EX-1 type ripoxy resin. Four-point bending test based on ASTM D-6272 standard with dimensions of specimen length 127 mm, width 12.7 ± 0.2 mm, thickness width 3.2 ± 0.2 mm and ASTM D-5941 impact toughness test , dimensions of rectangular specimens with a length of 80 ± 0.2 mm, width 10 ± 0.2 mm and thickness of 4.0 ± 0.2 mm. The results of the research are known the mechanical strength of bending test with a variation of polyester resin matrix, epoxy resin and ripoxy resin, the best in epoxy resin is 71.86 MPa, ripoxy resin is 66.00 MPa and polyester resin is 27.60 MPa and in impact toughness test, epoxy resin matrix of 6005 J/m, ripoxy resin of 5666 J/m and polyester resin of 5340 J/m.